Clinical Study on Immunostimulator (Lentinan) Administration in Patients with Inoperable Gastroenterological Cancer - OMORI, Hitoya; TAKEZAKI, Eiichi; TAKAISHI, Kenji; KAGAWA, Kazunori; NOMA, Koji (Japanese Journal of National Medical Services, 1988)
To evaluate the clinical effect of immunostimulator, the lentinan and chemotherapeutic agents were administered together in 9 patients with inoperable gastroenterological cancer (5 with hepatocellular cancer, 1 with cholangioma, 2 with pancreas cancer and 1 with advanced gastric cancer). The ratio of OKT 4/OKT 8 was increased because of the increment of OKT 4 activity and the decrease in OKT 8 activity during lentinan administration, suggesting that lentinan might influence as a immunomodulator. The successful efficacy of treatment was found in two cases with hepatocellular cancer and advanced gastric cancer. In those cases, the activity of NK cell maintained high levels or tended to increase during lentinan administration. The activity of Leu 7 and Leu 11 was correlated with the activity of NK cell, although it was difficult to conclude which of them was more reflected to the activity of NK cell in our subjects. In some cases with hepatocellular cancer, associated liver cirrhosis were fatal, suggesting that management of liver cirrhosis as well as treatment of cancer was important to improve the prognosis of cancer.